Design and Implementation of a Responsive E-Commerce Web Application for Teras Thrifting Store - Ulfiana, Riska Fitri; S.Kom., MT., Muhammad Najib Dwi Satria (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The rapid advancement of information technology has significantly impacted various sectors, including the trade industry. E-commerce has emerged as an innovation that enables buying and selling transactions to take place online, without limitations of location or time. However, some businesses—such as Teras Trifting, a second-hand clothing store—still rely on conventional transaction methods, such as in-store purchases or orders via social media messages. These approaches tend to be inefficient and prone to errors in recording customer and sales data. To address these challenges, this study focuses on the design and implementation of a responsive e-commerce web application aimed at improving transaction efficiency and the management of product and customer data. The system development process adopts the Extreme Programming (XP) methodology to ensure flexibility and adaptability to user needs. The application was developed using PHP and Bootstrap, with particular emphasis on user experience, system performance, and data security. Evaluation results show that the system achieved the following scores: functional suitability at 97.2%, performance efficiency at 94.8%, and usability at 93.84%, all classified as “Excellent.” Overall, the system attained a 94.82% feasibility score based on ISO 25010 standards, and is categorized as “Excellent” according to the Likert scale. In conclusion, this responsive e-commerce web application is considered to contribute positively to the business sector by enhancing competitiveness and operational efficiency within the digital ecosystem.